TRANSFORMASI PERAN GURU DALAM PENDIDIKAN ERA DIGITAL: SEBUAH SYSTEMATIC LITERATURE REVIEW TENTANG ADAPTASI PEDAGOGIK DAN LITERASI TEKNOLOGI - Heni Suryani (Pusat Pengembangan Pendidikan dan Penelitian Indonesia, 2026)
Technological literacy and teachers’ digital competence constitute key elements in the transformation of education in the digital era. This article aims to comprehensively analyze the concepts, challenges, and strategies for strengthening teachers’ technological literacy through a literature review method based on recent national and international scholarly publications. The synthesis findings indicate that technological literacy extends beyond technical skills in operating digital devices; it also encompasses pedagogical competence, digital ethics, professional identity management, and the capacity to adapt to emerging innovations such as artificial intelligence. Variations in teachers’ digital competence levels are influenced by factors including professional experience, institutional policy support, and access to continuous professional development and training. The enhancement of technological literacy has been shown to be effective through practice-based professional development programs, technology mentoring, and the systematic integration of digital pedagogical strategies. Furthermore, institutional support and adaptive educational policies play a decisive role in accelerating the transformation of teachers’ digital competencies. Overall, technological literacy and teachers’ digital competence represent a multidimensional construct that must be continuously developed to foster innovative, effective, and relevant learning aligned with the demands of 21st-century education. ABSTRAKLiterasi teknologi dan kompetensi digital guru merupakan elemen kunci dalam transformasi pendidikan di era digital. Artikel ini bertujuan untuk menganalisis secara komprehensif konsep, tantangan, dan strategi penguatan literasi teknologi guru melalui metode literature review terhadap berbagai jurnal nasional dan internasional terkini. Hasil sintesis menunjukkan bahwa literasi teknologi tidak hanya mencakup kemampuan teknis dalam mengoperasikan perangkat digital, tetapi juga meliputi kompetensi pedagogis, etika digital, manajemen identitas profesional, serta kemampuan adaptasi terhadap inovasi seperti kecerdasan buatan. Variasi tingkat kompetensi digital guru dipengaruhi oleh faktor pengalaman, dukungan kebijakan sekolah, serta akses terhadap pelatihan berkelanjutan. Penguatan literasi teknologi terbukti efektif melalui program pengembangan profesional berbasis praktik, pendampingan teknologi, dan integrasi strategi pedagogi digital yang sistematis. Selain itu, dukungan institusional dan kebijakan pendidikan yang adaptif menjadi faktor determinan dalam mempercepat transformasi kompetensi digital guru. Secara keseluruhan, literasi teknologi dan kompetensi digital guru merupakan konstruk multidimensional yang harus dikembangkan secara berkelanjutan guna mewujudkan pembelajaran yang inovatif, efektif, dan relevan dengan tuntutan abad ke-21.